Meningkatkan Pola Pengasuhan Otoritatif melalui Program Excellent Parenting - Rifa Hidayah (Universitas Negeri Surabaya, 2021)
Successful motherhood in educating children requires learning how to best care for children. Excellent parenting programs make it easier for mothers to better care for their children. The study aim was to examine the effect of